Different neoadjuvant therapies for locally advanced rectal cancer: A systematic review and network meta-analysis. (December 2022) - Petrelli, Fausto; Trevisan, Francesca; Tomasello, Gianluca; De Stefani, Agostina; Viti, Matteo; Garrone, Ornella; Luciani, Andrea; Ghidini, Michele
Abstract: One of the historical standard of care for locally advanced rectal adenocarcinoma (LARC) is neoadjuvant fluoropyrimidine-based chemoradiotherapy (FP-based CTRT) followed 6–8 weeks later by surgery. The incorporation of further chemotherapy cycles (CT) before or after CTRT (total neoadjuvant therapy) resulted in better outcomes than CTRT alone. Therefore, we performed a network meta-analysis (NMA) to compare the relative efficacy of different neoadjuvant treatments for LARC. Fixed-or random-effects models were fit using a Bayesian approach to NMA. Between-group comparisons were estimated using hazard ratios (HRs) or risk ratios (RRs) with 95 % credible intervals (95 % CrIs). A total of 23 randomized clinical trials were included. In Bayesian comparisons. FOLFIRINOX followed by capecitabine-based CTRT resulted in better OS than other regimens, including the previous standard, and ranked as the best regimen with a probability of 87 %. This NMA confirms that adopting total neoadjuvant therapy improves outcome compared to other preoperative strategies, including FP-based CTRT. Graphical Abstract: ga1 Highlights: This network meta-analysis found that induction FOLFIRINOX ranked as the best option in terms of overall survival for LARC. Chemotherapy doublets following CTRT resulted as the best treatment both in terms of disease-free survival. FOLFIRINOX followed by CTRT and (CT)RT + oxaliplatin-based CT resulted as the preferred options for LARC. Incorporation of total neoadjuvant therapy into the LARC management is emerging as the new standard of care.